Factors associated with depression among street vendors inside Kathmandu valley - Thapaliya, Roja; Chaudhary, Pramodh; Adhikari, Luna; Sangroula, Raj Kumar; Thapa , Janak (International Journal Of Community Medicine And Public Health, 2023)
Background: Depression is considered a common mental disorder and a major contributor to the global burden of disease. Depression is estimated to affect 3.8% of the population including 5% of adults and 5.7% among adults older than 60 years, and approximately 280 million people in the world (WHO 2021). Major symptoms of depression include depressed mood, loss of concentration, feeling of excessive guilt, dying thoughts, disrupted sleep, changes in appetite etc. Street vending is informal work that has been contributing in millions of people living status and supporting country’s economy. Methods: A cross-sectional analytical study was conducted among street vendors inside Kathmandu Valley with sample size 316. The study period was from August 2018 to April 2019. Data was collected using standard semi- structured tools using Kobo Toolbox. Data analysis was done in SPSS. Mendeley desktop and statistical package of social science software was used. Results: Out of 316 respondents, higher number were male i.e., 52.2% whereas females were 47.8%. Respondent with age group 25-35 years was high in number. Respondents engaged in street vending for 8-16 years were found high in number. 32.6% respondents had depressive symptoms while measuring with PHQ and the prevalence of depression was 55.4% which was measured using MDI. Conclusions: This cross-sectional study was conducted among the street vendors of Kathmandu valley. Among the respondents with low economic status, lack of physical activity, habit of alcohol and smoking had higher prevalence of depression. Respondent with basic and non- formal education, lack of job and income satisfaction showed a positive association with depression.